The Reflection of Society Culture in Visual Art Illustration of Javanese Manuscript - Nuning Damayanti Adisasmito (Institut Seni Indonesia Denpasar, 2018)
The tradition of writing and drawing in illustration was found in the old manuscript. Some parts of those old manuscripts show unique illustrations as well as the local identity of Nusantara’s society. The manuscript reflects the society culture of thinking and aesthetic achievement of visual art. The Illustrations of old Javanese manuscripts were well documented and has various representation in visualization art and style, drawing method, theme, and visual objects, even though the visualization of the visual concepts is practically similar to another. The illustration in the old Javanese manuscript in 1800-1920 shows continuous correlation of the visual language in the past era to the present and becomes the characteristics of Indonesian visual states. It reflects the structured illustration and style as well as expression symbol of the Javanese society in that era. Illustration of the old Javanese manuscript in the year 1800-1920 has changed and developed its visual state as the interaction between the animism in the Pre-Hinduism era, cultural paradigm of Hinduism-Buddhism, Islamic and Colonialism. The illustration style of the old Javanese manuscripts is decorative, naturalistic, realistic, simplified form and deformative.Tradisi menulis dan menggambar ilustrasi ditemukan pada manuskrip lama Nusantara. Sebagian dari manuskrip lama Nusantara itu memuat ilustrasi yang unik dan khas menjadi identitas masyarakat Nusantara. Naskah-naskah tersebut merefleksikan ketinggian budaya berpikir dan pencapaian estetik bidang seni rupa pada masyarakat Jawa dimasa itu. Sejumlah Manuskrip Jawa kuno didokumentasi dengan cukup baik, diantaranya merepresentasikan konsepsi seni dan ga-ya hidup pada masanya, juga memuat metode menggambar, objek visual, tema, dan konsep estetik yang tampaknya memiliki kesamaan satu dengan yang lain. Hasil analisis pada Ilustrasi yang dipilih dalam manuskrip Jawa periode tahun 1800-1920 menunjukkan adanya benang merah yang muncul secara terus-menerus bahkan hingga saat ini. Wujud visual art ilustrasi menjadi ciri khas ilustrasi Indonesia, gaya ilustrasi yang terstruktur dan menjadi simbol ekspresi di era itu. Konsep estetik dan wujud visual Ilustrasi manuskrip Jawa kuno mengalami perubahan dan pengembangan menunjukan gambaran dinamisasi interaksi antara paradigma animisme era Pra-Hindu, budaya Hinduisme-Buddha, Islam dan Kolonialisme. Gaya ilustrasi manuskrip Jawa kuno adalah bentuk dekoratif, naturalistik, realistis, disederhanakan dan deformatif.